N-Acenoacenes: synthesis and solid-state properties - Wiesner, Thomas; Pardon, Marcel; Maier, Steffen; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2022)
Four N-acenoacenes were synthesized and analyzed for their optoelectronic properties and solid-state packings. Two of the regioisomeric acridinoacridines are TIPS-ethynylated, whereas the other pair are Boc- and triflate substituted derivatives. The two TIPS-ethynyldiazaacenoacenes were processed into organic thin-film transistors with saturation hole mobilities reaching 2.9x10‑2cm2 (Vs) ‑1 .
Gesehen am 13.10.2022